Cost-effectiveness and economic analysis of antibiotics: a comprehensive study utilizing ICER and ACER metrics - Prajnashree Acharya; Someshwar S. Karabasanawar; Anurag R. Sattigeri; Vasudev P. Pai; Laxmi B. Totar; Sanatkumar Bharamu Nyamagoud (MGM Journal of Medical Sciences)
Background: Cost-effectiveness analysis (CEA) is a valuable tool in healthcare used to evaluate the economic efficiency of antibiotic treatments by comparing their costs with clinical outcomes, such as cost per life saved or quality-adjusted life days (QALDs) gained. This approach aids in informed decision-making, highlights price variations, and identifies patient groups likely to benefit most from specific treatments. Antibiotics frequently assessed in CEA include penicillins, cephalosporins, macrolides, fluoroquinolones, tetracyclines, and sulphonamides. While antibiotics have revolutionized healthcare, their efficacy is increasingly threatened by antimicrobial resistance (AMR) due to overuse and misuse. Aims and Objectives: The study aimed to evaluate the pharmacoeconomic impact of antibiotic treatments using CEA in a healthcare setting, focusing on identifying cost-effective antibiotics and promoting rational prescribing practices. Materials and Methods: A six-month observational study was conducted at Vivekananda General Hospital, Hubballi, Karnataka, involving 212 inpatients from general medicine wards. The study, approved by an ethics committee, utilized medical record analysis to assess the pharmacoeconomic impact of antibiotics through CEA. Key metrics included the average cost-effectiveness ratio (ACER) and incremental cost-effectiveness ratio (ICER). Results: Ciprofloxacin emerged as the most cost-effective intravenous antibiotic (ACER: 6.62 INR/QALD), while meropenem was the least cost-effective (ACER: 179.66 INR/QALD). Among oral antibiotics, doxycycline demonstrated the highest cost-effectiveness (ACER: 1.86 INR/QALD), whereas rifaximin was the least cost-effective (ACER: 13.18 INR/QALD). ICER analysis further highlighted azithromycin (0.56 INR/QALD) and amikacin (26.42 INR/QALD) as cost-effective choices. Conclusion: This study emphasizes the utility of CEA in optimizing antibiotic utilization, promoting rational prescribing practices, and supporting antimicrobial stewardship initiatives to safeguard antibiotic effectiveness in the face of rising AMR.